NPM1, FLT3-ITD, CEBPA, and c-kit mutations in 312 Chinese patients with de novo acute myeloid leukemia. Issue 6 (September 2014) - Su, Long; Gao, Su Jun; Li, Wei; Tan, Ye Hui; Cui, Jiu Wei; Hu, Rui Ping
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives To explore NPM1, FLT3-ITD, CEBPA, and c-kit mutations in patients with acute myeloid leukemia (AML) from Chinese population. Methods In this study, we retrospectively analyzed the prevalence and clinical proﬁle of NPM1, FLT3-ITD, CEBPA, and c-kit mutations in 312 patients with de novo AML. Results The frequencies of NPM1, FLT3-ITD, c-kit, and CEBPA mutations were 15.4, 14.0, 7.64, and 25.6%, respectively. The occurrence rate of NPM1 mutations increased with age in patients younger than 60 years. NPM1, c-kit, and CEBPA mutations were all associated with French-American-British subtypes. Patients with NPM1 mutations and FLT3-ITD presented with higher peripheral white blood cell counts and marrow blast percentages. Conclusion Both this and previous studies may suggest low frequencies of NPM1 and FLT3-ITD mutations in AML patients from the Chinese population, and they may have a synergistic function in stimulating proliferation of leukemia cells.